Minke’s Cultural Formation of Postcolonial Nationalism in Toer’s Anak Semua Bangsa - Simon Arsa Manggala; Gabriel Fajar Sasmita Aji; Sri Mulyani (UIN Raden Mas Said Surakarta, 2026)
The second novel of Pramoedya Ananta Toer’s Buru Tetralogy, entitled Anak Semua Bangsa, uplifts cultural formation of the main and prominent character, Minke, especially in dealing with his postcolonial nationalism. Minke’s encounters with various people and cultures impact his worldview in becoming pribumi, or local, of Indonesian people. This research frames the analysis in the light of cultural formation theory, which scrutinizes the dominant, residual, and emergent cultures. Here, Minke’s postcolonial efforts are in accordance with his growing sense of Indonesian nationalism. They cover such as analyzing the position of being marginalized, the resistance, and also the creation of space. Therefore, postcolonial approach is applied towards the data provided by the text of Anak Semua Bangsa. The findings show that Minke’s nationalism is triggered more by the awareness of being marginalized due to his status of being local, or the colonized, by the dominant power of the colonizer. Minke’s resistance against the oppressed authority drives him to embrace of being educated and qualified. Meanwhile, the creation of space is about gaining opportunity to expose his postcolonial writings, which imply his freedom of voicing and also bringing the awareness for the colonized Indonesian people. The research concludes that Minke’s postcolonial nationalism is the result of complex interplay of several aspects, i.e. capital powers, identity formation, and cultural encounters.